Pendampingan Kelompok Usaha Stik Nanas dalam Standarisasi Kemasanuntuk Meningkatkan Daya Saing - Kamil, Firmanilah; Nova Zulfahmi, A.; Dwi Hastuti, Ningrum (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
In addition to producing food products that are safe for consumption, food producers are also required to produce high quality products to meet consumer satisfaction. However, in reality, there are still many economic actors who do not understand how to improve and maintain the quality of their products. The second problem found by researchers in the pineapple stick business group is the lack of attractiveness of the product packaging offered. The purpose of this service activity in the form of training and mentoring is to help partners, in this case the pineapple stick production business group, to determine good packaging to extend shelf life, determine product packaging designs that can attract consumers' attention, and help business groups obtain NIB. Problem solutions are carried out in two stages of activity, namely preparation and implementation. The preparation stage is carried out with pre-survey activities, socialization and coordination of activities, preparation of work programs, preparation of training modules, and preparation of facilities and infrastructure during training and mentoring. The implementation phase is carried out in the order of socialization activities and assistance in the use of packaging materials, packaging design training and assistance, business group legality assistance, and ends with monitoring and evaluation.